Manufacture of Non-Contact Hand Washing Equipment as a Prevention of Transmission of the SARS Cov-2 Virus at the Al-Buchari Mosque, Johor Building Village, Medan Johor District, Medan City - Azhari; Nasution, Tulus Ikhsan; Banurea, Rahmadhani; Noer, Zikri; Sudiati; Hakim, Lukman; Piliang, M.Rifai (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Society of Lingkungan VIII Kelurahan Gedung Johor, Medan City utilizes the Al-Buchari Mosque as a means of worshiping and gaining knowledge for the Muslim community. However, Al-Buchari Mosque still uses water containers to wash the hands of its worshipers in order to prevent the transmission of the Sars-Cov 2 virus, which is an increasingly worrying situation. Medan Johor District is a red zone area in terms of the spread of the Sars-Cov 2 Virus. Based on data from the Corona Pandemic Prevention Task Force, Medan City has had more than 1000 positive cases of Covid-19 in the city of Medan. This is due to the lack of public awareness of the importance of washing hands, maintaining distance, and wearing masks. One of the effective ways to prevent the transmission of the Sars Cov-2 virus is to create a sink that does not require us to hold it but control it with our feet. So that the spread of the virus through hand media can be avoided. With this non-contact hand washing, people who worship at the Al-Buchari Mosque will minimize the transmission of the Sars Cov-2 virus through hand media.